Meningkatkan Hasil Belajar Siswa melalui Model Example Non Example pada Pembelajaran PAI di SDS BKMT Annisa KA. Tungkal - Daniati, Nia; Santi, Ika Nurmaya; Yuniarti, Efi (Asian Journal of Early Childhood and Elementary Education, 2025)
This study aims to examine the effectiveness of the Example Non Example learning model in improving students' learning outcomes in Islamic Education (PAI) at elementary school level. The Example Non Example model is used to teach Islamic concepts more clearly by comparing examples that align and do not align with Islamic teachings. This research adopts a quantitative approach with an experimental design, involving pretest and posttest to measure the difference in students' learning outcomes before and after the implementation of the learning model. The sample consisted of 30 students, and the learning process was carried out over 6 weeks. The results of data analysis revealed a significant improvement in students' learning outcomes after the implementation of the Example Non Example model. These findings indicate that this learning model is effective in enhancing students' understanding and learning outcomes in the subject of Islamic Education. The implications of this study provide a contribution to the development of more interactive and effective PAI learning strategies at the elementary school level.